2019
DOI: 10.1186/s42483-019-0039-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel gene from a secondary metabolism gene cluster is required for microsclerotia formation and virulence in Verticillium dahliae

Abstract: Verticillum dahliae is a notorious plant pathogenic fungus, which can cause wilt disease on hundreds of plant species. The genome of V. dahliae has been sequenced and annotated, but incorrect gene annotations and unidentified transcribed regions persist. Using RNA-Seq combined with reverse-transcription PCR, we identified a novel transcribed gene, Nag1, located in a cluster of putative secondary metabolic genes whose roles remain unknown. Functional analysis of Nag1 by dsRNA-mediated gene silencing revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…The analyses could not link this cluster to any previously known cluster. However, it has been proven that the nag 1 gene identified in this cluster is involved in the pathogenicity of V. dahliae [ 108 ]. Functional analysis of nag 1 by dsRNA-mediated gene silencing showed that the lack of nag 1 exponentially reduced conidial production and fungal growth.…”
Section: Discussionmentioning
confidence: 99%
“…The analyses could not link this cluster to any previously known cluster. However, it has been proven that the nag 1 gene identified in this cluster is involved in the pathogenicity of V. dahliae [ 108 ]. Functional analysis of nag 1 by dsRNA-mediated gene silencing showed that the lack of nag 1 exponentially reduced conidial production and fungal growth.…”
Section: Discussionmentioning
confidence: 99%
“…To observe the microsclerotia formation, Vd991, Δ VdDrs2 , and Com were cultured for 2 weeks on the CZA plates as described previously ( Xiong et al, 2019 ). The colony samples were directly imaged with a scanning electron microscope S-3400N (Hitachi, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…VdMcm1 also controls PKS/NRPs hybrid-cluster gene expression. Deletion of Nag-1 in this cluster results in defects in growth, virulence, and melanin biosynthesis [ 97 ]. The Vayg1 gene, a homolog of Aayg1 from Aspergillus fumigatus (Aayg1), is also required for both melanin and microsclerotia production in V. dahliae [ 93 ].…”
Section: Current Knowledge On Verticillium Dahliae mentioning
confidence: 99%